Financial Inclusion as a Silver Bullet in Poverty Reduction: A Longitudinal Data Case Study - Asep Yusup Hanapia; Jumri; Iis Surgawati; Novi Mela Yuliani; Asep Muhammad Adam; Meliani Mukti (Jurnal Ekonomi Pembangunan, 2025)
Poverty reduction remains a critical challenge in developing economies, including Indonesia, despite robust economic growth and financial sector expansion. This study investigates the impact of financial inclusion, financial literacy, and socio-economic characteristics on household poverty. Utilizing longitudinal data from the fifth wave of the Indonesia Family Life Survey, the analysis focuses on a sample of 2,222 households. Poverty is operationalized through the Multidimensional Poverty Index (MPI), encompassing health, education, and living standards, while financial inclusion is measured via a financial deprivation index across four dimensions: transactions, savings, credit, and insurance. Using logistic regression to account for the non-linearity of binary outcomes, the results indicate that both financial inclusion and financial literacy significantly reduce the probability of household poverty. These findings suggest that access to and understanding of formal financial services are vital for enhancing economic resilience. Furthermore, education and age are negatively associated with poverty, underscoring the role of human capital. Conversely, larger household sizes and rural residency increase poverty risk, highlighting structural vulnerabilities and spatial inequalities. While industrial participation mitigates poverty, agricultural dependence and limited market access remain significant constraints. These results emphasize the need for integrated policies that strengthen financial inclusion, promote literacy, and improve rural infrastructure to foster sustainable poverty reduction in Indonesia.